Analisis Faktor-faktor Yang Mempengaruhi Minat Pelaku UMKM Dalam Menggunakan Islamic Fintech - Khalila Husna Sari; Rifqi Muhammad; Anwar Sholihin; Sinky Adella (Jurnal Ilmiah Ekonomi Islam, 2023)
Islamic financial technology, also known as Islamic Fintech, has evolved throughout time in the financial industry, particularly in terms of financial technology innovation. It is a tool to boost the economics of Small and Medium Enterprises (SME), which naturally also takes Shari'ah principles into consideration. This research is motivated by lack of interest by Small and Medium Enterprise (SME) on using advance technology in financial sector for example Islamic fintech. Using Technology Acceptence Model (TAM) as model to predict the acceptance or use of technology by users and their benefits in work. Because of that researcher interested on finding what is the motivation of Small and Medium Enterprise (SME) on using advance technology such as Islamic Fintech as their financial source. Sampling method used in this research is cluster/ area sampling. Samples used in this study are 1121 Small and Medium Enterprise (SME) who are live in Bukittinggi. The result of this research are effectiveness, is not affected people interest on using Islamic Fintech. As for usefulness, ease to use, security risk, digital literacy, and infrastructure availability are affecting people interest in using Islamic Fintech.